(untitled) (Economics and region, 2022)
Business tourism is the most promising area of tourism activity, but at the same time it is strongly influenced by external and internal factors. The state of business tourism in a country can serve as a guide to the general trends and prospects for the development of the business environment. Today, Ukraine has temporarily suspended the provision of most popular types of tourist services, but there is a growing interest of foreign investors in business and diplomatic tourism. The purpose of the article is to analyze the latest pre- and post-crisis trends in the global business tourism industry and to determine the conditions for the recovery of the national business travel market. The subject of the study is the peculiarities of the functioning of the business tourism industry in the crisis and post-crisis period, the subject is to ensure the development of destinations in the field of business travel. The relevance of the study lies in the need to theoretically substantiate the strategies and prospects for the recovery of the national economy after the stagnation of 2020–2023. The article poses the problem of analyzing the categorical apparatus and features of interdisciplinary research in the field of business tourism in dynamics, with an emphasis on driving changes in global and national markets; the following tasks are solved: a comparative analysis of statistical indicators of the international travel sector in the pre- and post-covid period; differences in the factors of intensification of business and other types of tourism are identified; the concept of destination is clarified with regard to the needs of strategic planning of cooperation in the field of inter-sectoral cooperation; periodization of business tourism categories depending on the status of the destination life cycle is proposed; conditions for the resumption of business travel and requirements of modern consumers of the corporate segment are presented. Prospects for further research include studying the examples of countries with different levels of development that have overcome crisis trends by attracting investment from the business sector, and then using these experiences in the context of restoring Ukraine’s tourism infrastructure.